2006
DOI: 10.1007/s10661-005-9100-x
|View full text |Cite
|
Sign up to set email alerts
|

Northern Rivers Ecosystem Initiative: Distribution and Effects of Contaminants

Abstract: In response to a number of recommendations following the Northern Rivers Basin Studies (NRBS) contaminant program, the Northern Rivers Ecosystem Initiative (NREI) focused considerable attention on assessing contaminants from specific sources including pulp mill effluents, atmospheric transport of mercury and the Alberta oil sands operations. NRBS identified a number of major contaminants of concern including polychlorinated biphenyls, dioxins and furans, mercury and various hydrocarbons. Together, the NRBS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Detailed examination of the results revealed that there were deviations from the baseline at about 25% of the sites for one or more of the water quality parameters evaluated, but there were no consistent trends for which constituents were elevated. Other studies (e.g., Headley et al 2005;McMaster et al 2006a;Conly et al 2007) also concluded that high concentrations of arsenic (Conly et al 2007), metals (Headley et al 2005), and hydrocarbons (McMaster et al 2006a) were of natural origin. Several studies have been critical of the RAMP conclusions.…”
Section: Oil Sands Examplementioning
confidence: 96%
“…Detailed examination of the results revealed that there were deviations from the baseline at about 25% of the sites for one or more of the water quality parameters evaluated, but there were no consistent trends for which constituents were elevated. Other studies (e.g., Headley et al 2005;McMaster et al 2006a;Conly et al 2007) also concluded that high concentrations of arsenic (Conly et al 2007), metals (Headley et al 2005), and hydrocarbons (McMaster et al 2006a) were of natural origin. Several studies have been critical of the RAMP conclusions.…”
Section: Oil Sands Examplementioning
confidence: 96%
“…The various processes involved in bitumen extraction are believed to have environmental impacts on the area's water (McMaster et al, 2006), soil (Whitfield et al, 2009), and ecology (Goff et al, 2013). While air quality studies are much more limited (Hodson, 2013;, gaseous emissions such as SO 2 and NO x are known pollutants associated with oil sands activities (Charpentier and Bergerson, 2009;Bytnerowicz et al, 2010;McLinden, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the nearby Wapiti River, a tributary to the Peace River, a pulp mill was identified as the source of PCBs, but on the Athabasca River, the combined municipal sewage/mill effluent at the town of Hinton, AB, added little to high concentrations found upstream of the effluent, and the source is not known. Concentrations of PCBs did not decline during the NRBS/NREI studies, and remain an issue of concern, although as of 2004, concentrations did not exceed guidelines in any area (McMaster et al 2006). As in the case of dioxins and furans, biomagnification in food chains can result in high concentrations of PCBs in fish.…”
Section: Mercurymentioning
confidence: 95%
“…The recommended health study in the region was not done. After dioxins and furans were eliminated from mill effluents, concentrations in fish slowly declined (McMaster et al 2006), allowing the repeal of consumption advisories in the early 2000s. The NRBS program was very popular with stakeholders in the basin, because all sectors of society, including indigenous people, had direct input to an independent, transparent decision-making agency with a strong scientific advisory board consisting of several reputable independent scientists, led by Dr. Peter Larkin.…”
Section: The Northern River Basins and Northern Rivers Ecosystem Initmentioning
confidence: 99%
See 1 more Smart Citation